Bacillus amyloliquefaciens CU33 Fermented Product Improves Growth Performance, Diarrhea, and Immunity of Goat Kids - Tsung-Yu Lee; Yueh-Sheng Lee; Chean-Ping Wu; Bor-Chun Weng; Kuo-Lung Chen (Animals)
This study focused on the physicochemical characteristics of the fermented products (FP) produced by Bacillus amyloliquefaciens CU33 (CU33) from soybean meal with 70% moisture. Additionally, it investigated the effects of adding FP to starter on the growth performance, general health performance, blood clinical biochemistry, and immunity of Alpine goat kids during the weaning period. Forty 14-day-old male Alpine goat kids were randomly assigned into starter supplementations of 0, 0.1, 0.3, or 0.5% CU33 FP for 8 weeks, and each goat kid was individually raised in stainless steel cage (width 70 cm × height 70 cm × depth 80 cm). The moisture after fermentation was linearly decreased as fermentation time increased (p < 0.05), and the pH value and Bacillus-like counts reached the highest at 24 h of fermentation. The activity of neutral protease and alkaline protease, the content of surfactin and γ-PGA, the viscosity, and the odor of CU33 FP were linearly increased as fermentation time increased (p < 0.05). The neutral protease activity, surfactin, γ-PGA, and viscosity increased after drying, whereas the moisture, pH value, Bacillus-like counts, and odor decreased (p < 0.05). During the pre-weaning period (0–4 weeks), the body weight gain (BWG) of the 0.1% CU33 FP group was higher than that of the control group (p < 0.05), and all CU33 FP groups showed a better feed conversion ratio (FCR) than the control group (p < 0.05). During the post-weaning period (4–8 weeks) and throughout the entire experimental period (0–8 weeks), the BWG and FCR of all CU33 FP groups were better than those of the control group (p < 0.05). Furthermore, both BWG and FCR improved linearly as the dietary level of CU33 FP increased (p < 0.05). Simultaneously, the fecal consistency index at 0–4 and 4–8 weeks and the coliform counts in the rectum at 4 weeks linearly decreased (p < 0.05), and the Bacillus-like counts in the rectum linearly increased at 4 and 8 weeks (p < 0.05). Phosphorous (P), total protein (TP), blood urea nitrogen (BUN) in serum at 8 weeks, and the oxidative burst capacity at 4 weeks linearly increased as the dietary level of CU33 FP increased, but the skin sensitization test showed a quadratic curve, and the 0.1% CU33 FP group had the lowest performance (p < 0.05). In conclusion, dietary supplementation with 0.1% of CU33 FP can improve the growth performance, diarrhea status, and oxidative burst capacity of Alpine goat kids, showing the potential to be a feed additive.